A Retroperitoneal Granular Cell Tumour Mimicking Gastric Outlet Obstruction (Journal of Surgical Sciences, 2021)
Granular cell tumour (GCT) is a rare entity which is thought to be of neural origin. It is usually benign in nature with characteristic histological features. The tumour can occur anywhere in the body with common sites being the tongue, skin, subcutaneous tissue, breast, etc. But a retroperitoneal GCT is extremely uncommon. We report the case of a 50 years old male with a retroperitoneal lump with features of gastric outlet obstruction. Ultrasonography and CT scan report were inconclusive. The tumour was completely resected and histologically confirmed as GCT. The immunohistochemistry came positive for S100. Though rare, retroperitoneal GCT can be encountered in surgical practice posing diagnostic difficulty. This case report may guide its effective management.Journal of Surgical Sciences (2021) Vol. 25(2) : 52-55